Trends in prevalence and disability-adjusted life years for refractive disorders in China and globally from 1990 to 2021: an analysis of the Global Burden of Disease Study 2021 - Fangfang Lai; Hongfang Xia; Liang Wang (Frontiers in Public Health)
ObjectivesThis study aimed to describe the temporal trends in the prevalence and disability-adjusted life years (DALYs) of refractive disorders (RD) in China and globally from 1990 to 2021 and provide predictions in China for the next decade.MethodsUtilizing open data from the Global Burden of Disease database (2021), this study conducted a comprehensive comparative analysis of the RD burden in China and globally, including changes in prevalence and DALYs. Joinpoint regression was employed to calculate the annual percentage change, the average annual percentage change, and its corresponding 95% confidence interval to reflect segmented trends in RD burden. The APC model was used to assess the net effects of age, period, and cohort. The ARIMA model was applied to predict future trends.ResultsThe temporal trend of the health burden of RD in China aligned with the global trend, though the magnitude of change was greater, and the gap between the two had been narrowing recently. In China, the age-standardized DALYs rate for the total population (per 100,000 population) decreased from 74 in 1990 to 66 in 2021 and was projected to fall to 29.43 by 2031. The age-standardized prevalence rate for the total population (per 100,000 population) was expected to decrease to 411.23 by 2031, down from 1568 in 1990 to 1468 in 2021. However, the number of cases and the crude rates of prevalence and DALYs exhibited upward trends. In terms of age-specific rates, older adults exhibited higher prevalence and DALYs rates than younger adults. Regarding gender stratification, females had higher prevalence and DALYs rates than males.ConclusionThe age-standardized rates of prevalence and DALYs for RD have decreased in recent years and may continue to decline over the next decade. However, the crude rates of prevalence and DALYs are on the rise. The health burden of RD remains substantial, with females and the older population bearing a higher burden than males and younger populations.